2017
DOI: 10.1038/s41598-017-17597-3
|View full text |Cite
|
Sign up to set email alerts
|

The AP-1 transcription factor JunB is required for Th17 cell differentiation

Abstract: Interleukin (IL)-17-producing T helper (Th17) cells are crucial for host defense against extracellular microbes and pathogenesis of autoimmune diseases. Here we show that the AP-1 transcription factor JunB is required for Th17 cell development. Junb-deficient CD4+ T cells are able to develop in vitro into various helper T subsets except Th17. The RNA-seq transcriptome analysis reveals that JunB is crucial for the Th17-specific gene expression program. Junb-deficient mice are completely resistant to experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 61 publications
4
80
0
Order By: Relevance
“…We further dissected the molecular mechanism by which IL4 and DTA-1 stimulation triggers the differentiation of na€ ve CD4 þ T cells into IL21-expressing CD4 þ T cells. To this end, we examined the mRNA expression of the transcription factors involved in transcription of IL21, including AP-1 transcription factors (35)(36)(37)(38). We found that Maf mRNA was increased by stimulation with IL4 and DTA-1 to a peak at 18 hours of stimulation ( Fig.…”
Section: Il4 Is Required For Dta-1-induced Il21-producing Tfh Cellsmentioning
confidence: 99%
“…We further dissected the molecular mechanism by which IL4 and DTA-1 stimulation triggers the differentiation of na€ ve CD4 þ T cells into IL21-expressing CD4 þ T cells. To this end, we examined the mRNA expression of the transcription factors involved in transcription of IL21, including AP-1 transcription factors (35)(36)(37)(38). We found that Maf mRNA was increased by stimulation with IL4 and DTA-1 to a peak at 18 hours of stimulation ( Fig.…”
Section: Il4 Is Required For Dta-1-induced Il21-producing Tfh Cellsmentioning
confidence: 99%
“…IL‐23 was demonstrated to directly regulate Blimp‐1 expression, synergizing with RORγt in the differentiation of Th17 cells during inflammation . BATF also played a key role in Th17 cell differentiation via binding the promoter regions of IL‐17A, IL‐17F, IL‐21, and IL‐22 . Nevertheless, cytokines, such as IL‐2 and IL‐27, were shown to inhibit Th17 cell differentiation .…”
Section: Phenotype and Differentiation Of Th17 Cellsmentioning
confidence: 99%
“…Recently we and other groups have reported that JunB is essential for the development of IL-17producing helper T (Th17) cells, and thus Junb-deficient mice are completely resistant to experimental autoimmune encephalomyelitis (EAE). [5][6][7] In addition, the transfer of CD45RB hi CD25 − CD4 + T cells from Junb-deficient mice to Rag1-deficient mice fails to induce colitis, 6 suggesting that JunB is indispensable for pathogenicity of T cells in these autoimmune diseases. On the other hand, it is unclear whether JunB in CD4 + T cells is involved in other inflammatory diseases such as those induced by innate immune cells.…”
Section: Introductionmentioning
confidence: 99%